Metal-free synthesis of 5-trifluoromethyltetrazoles. (13th April 2022) - Lin, Xi; Luo, Beibei; He, Wenqin; Lu, Qingkai; Li, Longjia; Zheng, Huirong; Wu, Wei; Weng, Zhiqiang
Graphical abstract: Abstract: An efficient transition-metal-free method for the synthesis of 5-trifluoromethyltetrazoles from arenediazonium tetrafluoroborates is reported, which relies on the use of trifluoroacetaldehyde N -tosylhydrazone as a convenient 2, 2, 2-trifluorodiazoethane source. The reaction proceeds in good to excellent yields and shows a high functional group tolerance.